PENGARUH LATIHAN HALF SQUAT DAN LATIHAN QUARTER SQUAT PADA KECEPATAN TENDANGAN DAN DAYA LEDAK OTOT TUNGKAI - Sulistyo, Wahyu (Pendidikan Dan Kepelatihan Olahraga, 2010)
The aim of this research is to see the comparison of training influence between half squat and quarter squat to speed kicks and blow up energy heels muscle. The type of the observation is real experiment with Randomized Control's observational design Pretest Posttest Design's Group. Total sample as much as 90 students of semester II from 1995 / 1996 academic year in JPOK FKIP UNS. The sample is divided becomes 3 groups. Division of this group is done by Matched Subject Ordinal Pairing bases to pretest of speed variable kicks. I. group to be given half squat's training with subject as much 30 attempts, group II. given by quarter squat's training by totals subject as much 30 attempts, meanwhile control group be not been given training and just follows to even essay with subject as much 30 attempts. The training up to 6 weeks, divided as 2 periods, each period up to 3 weeks. Meanwhile essays that is done as much 3 times, which is (1 ) before hit by conducts (pretest), (2 ) afters 3 week were given by conduct (posttest 1), (3 ) afters 6 week were hit by conduct (posttest 2). Pending variable that essaying to cover: speed kicks that is essayed ably do maximal speed kick and energy blows up heel's muscle that measured by vertical jump ability. The data is acquired with Systat's computer programming 5.0 and analyzed with statistical anava's quiz and quiz t by signifikans' level 5%. The conclusion of this research is:? The quarter squat?s training can increase the speed kicks and blow up energy heels muscle better than the half squat ?.